Pengaruh Penggunaan Media Instagram Terhadap Pelayanan Pengasuh ABK di Wisma Setaman Dalam - Siribere, Margaretha Jayusni; Goa, Lorentius (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
Instagram is a photo and video sharing application that is packaged attractively and is easy to apply. Instagram users will indirectly feel the impact of continued use of this social media. With the presence of Instagram media, people can easily take pictures anywhere and anytime and then post them on social media. This article aims to determine the influence of the use of Instagram media on caregivers in providing services to ABK and to find out what influence social media currently has, especially on the use of Instagram media. The method used is qualitative research, this research requires direct interaction with participants, is time consuming and collects small amounts of data. This research also uses a research process through interviews with caregivers because this research uses qualitative methods, the data collection techniques used are observation and interviews. Interviews were conducted face to face with caregivers at Wisma Setaman Dalam who used Instagram. After going through these processes, the author discovered a problem at Wisma Setaman Dalam, namely that Instagram was used irregularly and caregivers used Instagram as a comparison material for Instagram media with the ABK period, caregivers spent more time using Instagram media than in activities with the ABK. so that the activities at Wisma Setaman Dalam with the crew members were disrupted and did not run well and the crew members' talents did not develop well. In the next steps, joint activities with crew members and caregivers will be carried out in accordance with the provisions of the schedule at Wisma Setaman Dalam.